STRATEGI KOMUNIKASI PEMBINAAN AGAMA HINDU DALAM MENINGKATKAN SRADDHA DAN BHAKTI WARGA BINAAN PEMASYARAKATAN (WBP) HINDU DI LAPAS KLAS IIA DENPASAR - Guseka Arya Cyuta; I Dewa Ayu Hendrawathy Putri; Ida Ayu Tary Puspa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The communication strategy is planning and management to achieve one goal. Class IIA Denpasar Prison which plays a major role in conducting a coaching pattern that is closely related to the communication strategy for Correctional Assistants (WBP) is part of Child Guidance Correctional Education (Binadik) and the Work Activities Section. This research is a qualitative method in which the sample is taken by using the purposive sampling technique. The total number of informants was 10 people and the data were collected from field observations, documentation, and in-depth interviews. To reinforce, there are several concepts that will be explained in advance, including Communication Strategy, Development Model, Correctional Assistance (WBP), Sraddha and Bhakti, and Lapas. The results showed that the pattern of coaching at Class IIA Denpasar Prison applies a top down approach, namely by providing personality development including religious awareness development, legal awareness development, intellectual development, physical and spiritual health development, and a bottom up approach) for self-reliance development which includes work skills, where these work skills hone the soft skills possessed by WBP who are carried out in the center, and are still under the supervision of security officers in prisons.